Examining the influence of grip type on wrist and club head kinematics during the golf swing: Benefits of a local co-ordinate system. Issue 3 (16th March 2019) - Carson, Howie J.; Richards, Jim; Mazuquin, Bruno
Abstract: Wrist movements have been identified as an important factor in producing a successful golf swing, with their complex motion influencing both club head velocity and orientation. However, a detailed analysis of wrist angles is lacking in the literature. The purpose of this study was to determine kinematics across wrists and club head characteristics during the golf swing under weak, neutral and strong grip conditions. Twelve professional male golfers executed 24 shots using a driver under three grip conditions. A six degrees of freedom analysis of the hand with respect to the distal forearm was performed using a 10-camera three-dimensional motion capture system. Differences in joint angles were explored using repeated measures ANOVAs at key swing events (onset, top of backswing and impact), in addition club head velocity and clubface angle at impact were also explored. Main findings revealed significant differences in flexion/extension and internal/external rotation for both wrists at all swing events, whereas fewer significant interactions were found in ulnar/radial deviation across grips for both wrists at all events. Clubface angle only differed significantly between the weak and the strong and neural grips, presenting a more 'open' clubface to the intended hitting direction. This study is the first to explore tri-planar wrist movement and the effect of different grips, such analysis has implications for coaching knowledge and practice and should inform future research into different aspects of skill, technique analysis and may inform injury mechanisms/prevention.